Quick-drying water-based spraying marking paint and preparation method thereof
By leveraging the synergistic effect of microencapsulated stannous octoate and tertiary amine catalysts, combined with specific components, a fast-curing water-based sprayable road marking paint was prepared. This solves the problem of long construction time in traditional water-based road marking paints, achieving rapid curing and high-performance spraying effects, making it suitable for the field of road marking materials.
Patent Information
- Application Number
- CN202511303790.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-12
- Publication Date
- 2025-12-02
AI Technical Summary
Traditional water-based road marking paints have a long open time for traffic at room temperature and a slow curing speed at low temperatures in winter, making it difficult to meet the needs of rapid construction.
A rapid-curing spray marking paint is formed by using a synergistic catalytic system of microencapsulated stannous octoate and tertiary amine catalysts, combined with components such as hydroxyl acrylic dispersion, silane-modified nano-SiO2 and hollow glass microspheres.
It can be opened to traffic within 10-15 minutes at room temperature and cured within 30 minutes at low temperature, significantly shortening the sealing time, improving construction efficiency, providing a tough paint film and good wear resistance and reflectivity, suitable for winter construction, and is environmentally friendly and non-toxic.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to a fast-drying water-based sprayable road marking paint and its preparation method, belonging to the technical field of road marking materials. Background Technology
[0002] Traffic markings are an important component of the road traffic system, playing a vital role in ensuring road traffic safety and improving traffic efficiency. With the increasing emphasis on environmental protection, water-based road traffic markings are gradually attracting the attention of marking maintenance units.
[0003] Water-based road marking paints are mainly composed of resin emulsions, water, powders, and related additives. Their strength primarily relies on water evaporation and resin emulsion film formation. Since water evaporation takes time, it's difficult to expect rapid traffic reopening after water-based marking construction. Traditional water-based marking paints typically allow traffic to resume within 30-60 minutes at 25°C. In low winter temperatures, their slow curing speed generally discourages their use. Therefore, improving the performance of water-based marking paints to enable rapid drying and curing has become a key focus of water-based marking research. Summary of the Invention
[0004] The purpose of this invention is to provide a fast-drying water-based spray marking paint and its preparation method. This paint has the advantages of fast low-temperature curing, durability, and environmental friendliness.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A fast-drying water-based spray marking paint comprises the following components in parts by weight: 40-60 parts hydroxyl acrylic dispersion, 0.3-0.6 parts microencapsulated stannous octoate, 0.2-0.5 parts tertiary amine co-catalyst, 3-8 parts silane-modified nano-SiO2, 10-20 parts hollow glass microspheres, 0.5-2 parts wetting and dispersing agent, 2-5 parts low freezing point film-forming aid, 5-8 parts pigment, 0.1-0.5 parts defoamer, and 15-25 parts deionized water.
[0006] Preferably, the preparation method of microencapsulated stannous octoate involves mixing stannous octoate with methyl methacrylate to form an oil phase, which is then added dropwise to an aqueous phase obtained by mixing sodium dodecyl sulfate and deionized water after heating. After high-speed shearing to form a microemulsion, an initiator is added, and the reaction is carried out under nitrogen protection. The product is then cooled, filtered, dialyzed, and spray-dried.
[0007] Preferably, the mass ratio of stannous octoate to methyl methacrylate is 1:(2-3); the mass ratio of sodium dodecyl sulfate to deionized water is (1-5):100; and the mass ratio of aqueous phase to oil phase is 100:(50-70).
[0008] Preferably, the temperature of the aqueous phase after heating is 50-70℃; the high-speed shearing conditions are: 8000-15000 rpm, 10-20 min; and the reaction conditions are: 200-500 rpm, 70-80℃, 5-7 h.
[0009] Preferably, the tertiary amine co-catalyst is any one of triethylenediamine, dimethylethanolamine, and trimethylbenzylamine.
[0010] Preferably, the hollow glass microspheres are obtained by mixing borosilicate glass microspheres with a particle size of 100-150 μm and a particle size of 20-50 μm in a mass ratio of 1:(0.5-1.5). The refractive index of the borosilicate glass microspheres is 1.5-19, and the density is 0.15-0.25 g / cm³. 2 .
[0011] Preferably, the wetting and dispersing agent is one or more of the following: ammonium polyacrylate, ethylene oxide-propylene oxide block copolymer, alkylphenol polyoxyethylene ether phosphate, polyether-modified trisiloxane, and polyhydroxystearic acid-polyethylene glycol ester.
[0012] Preferably, the low freezing point film-forming aid is dipropylene glycol methyl ether; the pigment is rutile titanium dioxide or cadmium yellow.
[0013] Preferably, the defoamer is one or more of polydimethylsiloxane, polyether-polysiloxane copolymer, and C12-C14 fatty alcohol.
[0014] The preparation method of any of the above-mentioned fast-drying water-based spray marking paints involves mixing a hydroxyl acrylic dispersion with deionized water, adding epoxy silane-modified nano-SiO2, a wetting and dispersing agent, and an antifoaming agent, and then stirring. Next, microencapsulated stannous octoate, a tertiary amine co-catalyst, and a low-freezing-point film-forming aid are added and stirred again. Finally, hollow glass microspheres and pigments are added and stirred.
[0015] The beneficial effects of this invention are as follows: This coating dries extremely quickly after spraying, allowing for road reopening within 10-15 minutes at room temperature and rapid curing within 30 minutes at low temperatures. This significantly reduces road closure time, improves construction efficiency, and lowers overall costs, making it particularly suitable for winter application. Simultaneously, it rapidly forms a tough film, providing long-lasting high contrast, reflectivity, and abrasion resistance, ensuring driving safety. Furthermore, this water-based product is non-toxic, non-flammable, and has extremely low VOC content, making it environmentally friendly. Detailed Implementation
[0016] The preparation method of microencapsulated stannous octoate used in the following examples and comparative examples is as follows: 15g of stannous octoate was mixed with 45g of methyl methacrylate and sonicated for 10min to completely dissolve it, forming a homogeneous oil phase. 100g of deionized water and 3g of sodium dodecyl sulfate were added to a reaction vessel and stirred (500rpm) until completely dissolved, then heated to 60°C. The oil phase was slowly added dropwise to the aqueous phase while simultaneously shearing at high speed (10,000rpm, 15min) to form an O / W microemulsion with a particle size of approximately 100nm. Ammonium persulfate initiator was added, and the temperature was raised to 75°C under nitrogen protection, and the reaction was carried out for 6h. The stirring speed was maintained at 300rpm to avoid microcapsule aggregation. After the reaction was completed, the mixture was cooled to room temperature, filtered to remove a small amount of agglomerates, dialyzed three times with deionized water (to remove unreacted monomers and emulsifiers), and spray-dried to obtain white powder microcapsules with a particle size of 100-200nm.
[0017] The epoxy-based silane-modified nano-SiO2 used has a particle size of 10-50 nm and a specific surface area of 150-300 m². 2 / g, surface hydroxyl group density is 2-4 OH groups / nm 2 Nano-SiO2 coupled with silane coupling agent γ-(2-) , 3-Epoxypropoxy)propyltrimethoxysilane was pretreated to achieve a surface grafting rate of 60%-80%, and was purchased from Ingenic Semiconductor GmbH, Germany.
[0018] The molecular weight of the hydroxyacrylic acid dispersion used was 80,000~120,000 g / mol, and it was purchased from BASF.
[0019] Example 1: This example provides a fast-drying water-based spray marking paint, which is composed of the following raw materials in parts by weight: 50 parts of hydroxyl acrylic dispersion, 0.3 parts of microencapsulated stannous octoate, 0.2 parts of triethylenediamine, 5 parts of epoxy silane modified nano-SiO2 (particle size 10nm), 15 parts of borosilicate glass microspheres with a large particle size (100μm) to small particle size (20nm) mass ratio of 1:1, 1 part of ammonium polyacrylate, 3 parts of dipropylene glycol methyl ether, 6 parts of rutile titanium dioxide, 0.3 parts of polydimethylsiloxane, and 20 parts of deionized water.
[0020] The preparation method of the coating includes the following steps: S1: Place the hydroxyacrylic acid dispersion into a reaction vessel, then pour in deionized water, and stir at 2000 r / min for 15 min at room temperature; S2: Add epoxy silane modified nano-SiO2, ammonium polyacrylate, and dipropylene glycol methyl ether to the reactor in sequence, and stir at 2500 r / min for 10 min at room temperature; S3: Add microencapsulated stannous octoate, triethylenediamine, and polydimethylsiloxane, and stir at 500 r / min for 10 min at room temperature; S4: Continue to add borosilicate glass microspheres and rutile titanium dioxide, and stir at 1000 r / min for 15 min at room temperature. After stirring, you can obtain fast-drying water-based spray marking paint.
[0021] Example 2: This example provides a fast-drying water-based spray marking paint, which is composed of the following raw materials in parts by weight: 55 parts of hydroxyl acrylic dispersion, 0.4 parts of microencapsulated stannous octoate, 0.2 parts of dimethylethanolamine, 6 parts of epoxy silane modified nano-SiO2 (particle size 30nm), 15 parts of borosilicate glass microspheres with a large particle size (120μm) to small particle size (30nm) mass ratio of 1:1, 1 part of ammonium polyacrylate, 3 parts of dipropylene glycol methyl ether, 8 parts of rutile titanium dioxide, 0.3 parts of polydimethylsiloxane, and 25 parts of deionized water.
[0022] The preparation method of the coating includes the following steps: S1: Place the hydroxyacrylic acid dispersion into a reaction vessel, then pour in deionized water, and stir at 2000 r / min for 15 min at room temperature; S2: Add epoxy silane modified nano-SiO2, ammonium polyacrylate, and dipropylene glycol methyl ether to the reactor in sequence, and stir at 2500 r / min for 10 min at room temperature; S3: Add microencapsulated stannous octoate, triethylenediamine, and polydimethylsiloxane, and stir at 500 r / min for 10 min at room temperature; S4: Continue to add borosilicate glass microspheres and rutile titanium dioxide, and stir at 1000 r / min for 15 min at room temperature. After stirring, you can obtain fast-drying water-based spray marking paint.
[0023] Example 3: This example provides a fast-drying water-based spray marking paint, composed of the following raw materials in parts by weight: 60 parts hydroxy acrylic dispersion, 0.5 parts microencapsulated stannous octoate, 0.3 parts trimethylbenzylamine, 5 parts epoxy silane modified nano-SiO2 (particle size 50nm), 20 parts borosilicate glass microspheres with a large particle size (100μm) to small particle size (20nm) mass ratio of 1:1, 1 part polyether modified trisiloxane, 3 parts dipropylene glycol methyl ether, 6 parts rutile titanium dioxide, 0.3 parts polydimethylsiloxane, and 20 parts deionized water.
[0024] The preparation method of the coating includes the following steps: S1: Place the hydroxyacrylic acid dispersion into a reaction vessel, then pour in deionized water, and stir at 2000 r / min for 15 min at room temperature; S2: Add epoxy silane modified nano-SiO2, ammonium polyacrylate, and dipropylene glycol methyl ether to the reactor in sequence, and stir at 2500 r / min for 10 min at room temperature; S3: Add microencapsulated stannous octoate, triethylenediamine, and polydimethylsiloxane, and stir at 500 r / min for 10 min at room temperature; S4: Continue to add borosilicate glass microspheres and rutile titanium dioxide, and stir at 1000 r / min for 15 min at room temperature. After stirring, you can obtain fast-drying water-based spray marking paint.
[0025] Example 4: This example provides a fast-drying water-based spray marking paint, composed of the following raw materials in parts by weight: 60 parts hydroxy acrylic dispersion, 0.3 parts microencapsulated stannous octoate, 0.6 parts trimethylbenzylamine, 5 parts epoxy silane modified nano-SiO2 (particle size 20nm), 15 parts borosilicate glass microspheres with a large particle size (100μm) to small particle size (20nm) mass ratio of 1:1, 1 part ammonium polyacrylate, 5 parts dipropylene glycol methyl ether, 6 parts rutile titanium dioxide, 0.3 parts polydimethylsiloxane, and 22 parts deionized water.
[0026] The preparation method of the coating includes the following steps: S1: Place the hydroxyacrylic acid dispersion into a reaction vessel, then pour in deionized water, and stir at 2000 r / min for 15 min at room temperature; S2: Add epoxy silane modified nano-SiO2, ammonium polyacrylate, and dipropylene glycol methyl ether to the reactor in sequence, and stir at 2500 r / min for 10 min at room temperature; S3: Add microencapsulated stannous octoate, triethylenediamine, and polydimethylsiloxane, and stir at 500 r / min for 10 min at room temperature; S4: Continue to add borosilicate glass microspheres and rutile titanium dioxide, and stir at 1000 r / min for 15 min at room temperature. After stirring, you can obtain fast-drying water-based spray marking paint.
[0027] Example 5: This example provides a fast-drying water-based spray marking paint, composed of the following raw materials in parts by weight: 60 parts hydroxy acrylic dispersion, 0.3 parts microencapsulated stannous octoate, 0.6 parts triethylenediamine, 5 parts epoxy silane modified nano-SiO2 (particle size 20nm), 15 parts borosilicate glass microspheres with a large particle size (100μm) to small particle size (20nm) mass ratio of 1:1, 1 part ammonium polyacrylate, 5 parts dipropylene glycol methyl ether, 8 parts rutile titanium dioxide, 0.5 parts polydimethylsiloxane, and 22 parts deionized water.
[0028] The preparation method of the coating includes the following steps: S1: Place the hydroxyacrylic acid dispersion into a reaction vessel, then pour in deionized water, and stir at 2000 r / min for 15 min at room temperature; S2: Add epoxy silane modified nano-SiO2, ammonium polyacrylate, and dipropylene glycol methyl ether to the reactor in sequence, and stir at 2500 r / min for 10 min at room temperature; S3: Add microencapsulated stannous octoate, triethylenediamine, and polydimethylsiloxane, and stir at 500 r / min for 10 min at room temperature; S4: Continue to add borosilicate glass microspheres and rutile titanium dioxide, and stir at 1000 r / min for 15 min at room temperature. After stirring, you can obtain fast-drying water-based spray marking paint.
[0029] Comparative Example 1: This comparative example provides a fast-drying water-based spray marking paint, which is composed of the following raw materials in parts by weight: 50 parts of hydroxyl acrylic dispersion, 0.2 parts of triethylenediamine, 5 parts of epoxy silane modified nano-SiO2, 15 parts of borosilicate glass microspheres with a large particle size (100μm) to a small particle size (20nm) mass ratio of 1:1, 1 part of ammonium polyacrylate, 3 parts of dipropylene glycol methyl ether, 6 parts of rutile titanium dioxide, 0.3 parts of polydimethylsiloxane, and 20 parts of deionized water.
[0030] The preparation method of the coating includes the following steps: S1: Place the hydroxyacrylic acid dispersion into a reaction vessel, then pour in deionized water, and stir at 2000 r / min for 15 min at room temperature; S2: Add epoxy silane modified nano-SiO2, ammonium polyacrylate, and dipropylene glycol methyl ether to the reactor in sequence, and stir at 2500 r / min for 10 min at room temperature; S3: Add triethylenediamine and polydimethylsiloxane, and stir at 500 r / min for 10 min at room temperature; S4: Continue to add borosilicate glass microspheres and rutile titanium dioxide, and stir at 1000 r / min for 15 min at room temperature. After stirring, you can obtain fast-drying water-based spray marking paint.
[0031] Comparative Example 2: This comparative example provides a fast-drying water-based spray marking paint, which is composed of the following raw materials in parts by weight: 50 parts of hydroxyl acrylic dispersion, 0.3 parts of microencapsulated stannous octoate, 5 parts of epoxy silane modified nano-SiO2, 15 parts of borosilicate glass microspheres with a large particle size (100μm) to a small particle size (20nm) mass ratio of 1:1, 1 part of ammonium polyacrylate, 3 parts of dipropylene glycol methyl ether, 6 parts of rutile titanium dioxide, 0.3 parts of polydimethylsiloxane, and 20 parts of deionized water.
[0032] The preparation method of the coating includes the following steps: S1: Place the hydroxyacrylic acid dispersion into a reaction vessel, then pour in deionized water, and stir at 2000 r / min for 15 min at room temperature; S2: Add epoxy silane modified nano-SiO2, ammonium polyacrylate, and dipropylene glycol methyl ether to the reactor in sequence, and stir at 2500 r / min for 10 min at room temperature; S3: Add microencapsulated stannous octoate and polydimethylsiloxane, and stir at 500 r / min for 10 min at room temperature; S4: Continue to add borosilicate glass microspheres and rutile titanium dioxide, and stir at 1000 r / min for 15 min at room temperature. After stirring, you can obtain fast-drying water-based spray marking paint.
[0033] Comparative Example 3: This comparative example provides a fast-drying water-based sprayable road marking paint, composed of the following raw materials in parts by weight: 50 parts hydroxyl acrylic dispersion, 5 parts epoxy silane-modified nano-SiO2, 15 parts borosilicate glass microspheres with a large particle size (100 μm) to a small particle size (20 nm) mass ratio of 1:1, 1 part ammonium polyacrylate, 3 parts dipropylene glycol methyl ether, 6 parts rutile titanium dioxide, 0.3 parts polydimethylsiloxane, and 20 parts deionized water. The preparation method includes the following steps: S1: Place the hydroxyacrylic acid dispersion into a reaction vessel, then pour in the specified proportion of deionized water, and stir at 2000 r / min for 15 min at room temperature; S2: Add epoxy silane modified nano-SiO2, ammonium polyacrylate, and dipropylene glycol methyl ether to the reactor in sequence, and stir at 2500 r / min for 10 min at room temperature; S3: Add polydimethylsiloxane and stir at 500 r / min for 10 min at room temperature; S4: Continue to add borosilicate glass microspheres and rutile titanium dioxide, and stir at 1000 r / min for 15 min at room temperature. After stirring, you can obtain fast-drying water-based spray marking paint.
[0034] Comparative Example 4: The material composition was as follows: 350 parts of waterborne acrylic resin emulsion (55% solid content), 0.6 parts of industrial-grade ammonia, 2.5 parts of perfluoroalkyl ether, 1.5 parts of hydroxylated heptane defoamer, 100 parts of rutile titanium dioxide, 650 parts of heavy calcium carbonate (800 mesh), 30 parts of methanol (CAS No.: 67-56-1), 20 parts of dodecyl alcohol ester (CAS No.: 25265-77-4), and hydroxyethyl cellulose (molecular weight 9×10⁻⁶). 4 - 7×10 6 g / mol, CAS No.: 9004-62-0) 3.5 portions.
[0035] Its preparation method includes the following steps: S1: At room temperature and pressure, add the water-based acrylic resin emulsion into the reactor, along with perfluoroalkyl ether and hydroxylated heptane defoamer, and stir at 800 rad / min for 5 min.
[0036] S2: Continue to add industrial-grade ammonia, methanol, dodecyl alcohol ester, and hydroxyethyl cellulose to the reactor, and stir at 1200 rad / min for 10 min.
[0037] S3: Continue to add rutile titanium dioxide and heavy calcium carbonate to the reactor, and stir at 1200 rad / min for 10 min.
[0038] Comparative Example 5: The material composition is 420 parts of epoxy modified acrylic emulsion (solid content 50%), 0.6 parts of industrial grade ammonia, 2.5 parts of polyether modified polysiloxane, 1.5 parts of polyoxypropylene glycerol ether, 150 parts of titanium dioxide, 600 parts of heavy calcium carbonate, 30 parts of methanol, 25 parts of dodecyl alcohol ester, and 3.5 parts of hydroxyethyl cellulose.
[0039] Its preparation method includes the following steps: S1: At room temperature and pressure, add epoxy-modified acrylic emulsion into the reactor, and simultaneously add polyether-modified polysiloxane and polyoxypropylene glycerol ether, and stir at 800 rad / min for 5 min.
[0040] S2: Continue to add industrial-grade ammonia, methanol, dodecyl alcohol ester, and hydroxyethyl cellulose to the reactor, and stir at 1200 rad / min for 10 min.
[0041] S3: Continue to add rutile titanium dioxide and heavy calcium carbonate to the reactor, and stir at 1200 rad / min for 10 min.
[0042] Performance Testing: Based on the preparation of the coatings in the examples and comparative examples, each coating was used for relevant performance testing. Specific test items included -10℃ non-stick drying time, abrasion resistance, adhesion, water resistance, and artificially accelerated weathering resistance. The abrasion resistance, adhesion, water resistance, and artificially accelerated weathering resistance indicators and their test methods were performed according to standard JT / T 280-2022. For the -10℃ non-stick drying time test, sample preparation and testing methods were performed according to standard JT / T 280-2022, and the samples were cured at -10℃.
[0043] The performance of the coatings obtained in each embodiment was tested, and the results are shown in Table 1. Table 1 shows that the curing time of the coating is very slow when no main catalyst or co-catalyst is added; if no catalyst is added at all, the coating does not cure. Furthermore, as other formulations, the coatings in Comparative Examples 4 and 5 also have relatively long non-stick drying times. In summary, the five embodiments provided in this application, while possessing good abrasion resistance, adhesion, water resistance, and weather resistance, also have shorter non-stick drying times and significantly faster curing speeds, making them more suitable for water-based lane marking in low-temperature environments.
[0044] Table 1. Test results of coatings obtained from different embodiments and comparative examples.
[0045] By testing the coating performance in the examples and comparative examples, it was found that the drying time of the coatings in the examples at -10℃ was shorter than that in the comparative examples, indicating that the coatings provided in this application are more conducive to curing at low temperatures. The mechanism is as follows: using a tin-amine synergistic catalytic system, two reactions are simultaneously catalyzed at low temperatures. One is the catalytic hydrolysis and condensation of silanyl methoxy groups on the silane-modified nano-SiO2. The other is the catalytic ring-opening etherification reaction between the epoxy groups at the silane terminus and the hydroxyl groups on the hydroxyl acrylic resin, forming a stable COC covalent bond.
[0046] The aqueous hydroxyl acrylic dispersion contains active functional groups (-OH), providing a basis for potential subsequent cross-linking reactions. The modifier for nano-SiO2 is γ-(2,3-epoxypropoxy)propyltrimethoxysilane. One end (trimethoxysilane) can be hydrolyzed and grafted onto the surface of nano-SiO2, while the other end (epoxy group) can undergo ring-opening reaction with the hydroxyl groups of the resin under the action of a catalyst. Through these reactions, nano-SiO2 acts as a cross-linking point, connecting linear acrylic resin molecules into a three-dimensional network structure, thereby achieving low-temperature catalytic cross-linking. This not only significantly accelerates the "drying" speed of the coating film but also greatly improves its final hardness, abrasion resistance, adhesion, and other mechanical properties.
Claims
1. A quick-drying water-based sprayable road marking paint, characterized in that, The product comprises the following components in parts by weight: 40-60 parts hydroxy acrylic acid dispersion, 0.3-0.6 parts microencapsulated stannous octoate, 0.2-0.5 parts tertiary amine co-catalyst, 3-8 parts epoxy silane modified nano-SiO2, 10-20 parts hollow glass microspheres, 0.5-2 parts wetting and dispersing agent, 2-5 parts low freezing point film-forming aid, 5-8 parts pigment, 0.1-0.5 parts defoamer, and 15-25 parts deionized water.
2. The quick-drying water-based sprayable road marking paint according to claim 1, characterized in that, The preparation method of microencapsulated stannous octoate involves mixing stannous octoate with methyl methacrylate to form an oil phase, which is then added dropwise to an aqueous phase obtained by mixing sodium dodecyl sulfate and deionized water after heating. After high-speed shearing to form a microemulsion, an initiator is added, and the reaction is carried out under nitrogen protection. The mixture is then cooled, filtered, dialyzed, and spray-dried.
3. The quick-drying water-based sprayable road marking paint according to claim 2, characterized in that, The mass ratio of stannous octoate to methyl methacrylate is 1:(2-3); the mass ratio of sodium dodecyl sulfate to deionized water is (1-5):100; and the mass ratio of aqueous phase to oil phase is 100:(50-70).
4. The quick-drying water-based sprayable road marking paint according to claim 2, characterized in that, The temperature of the aqueous phase after heating is 50-70℃; the conditions for high-speed shearing are 8000-15000 rpm for 10-20 min; the conditions for reaction are 200-500 rpm for 70-80℃ for 5-7 h.
5. The quick-drying water-based sprayable road marking paint according to claim 1, characterized in that, The tertiary amine cocatalyst is any one of triethylenediamine, dimethylethanolamine, and trimethylbenzylamine.
6. The quick-drying water-based sprayable road marking paint according to claim 1, characterized in that, Hollow glass microspheres are obtained by mixing borosilicate glass microspheres with a particle size of 100-150μm and a particle size of 20-50μm in a mass ratio of 1:(0.5-1.5).
7. The quick-drying water-based sprayable road marking paint according to claim 1, characterized in that, The wetting and dispersing agent is one or more of the following: ammonium polyacrylate, ethylene oxide-propylene oxide block copolymer, alkylphenol polyoxyethylene ether phosphate, polyether-modified trisiloxane, and polyhydroxystearic acid-polyethylene glycol ester.
8. The quick-drying water-based sprayable road marking paint according to claim 1, characterized in that, The low-freezing-point film-forming aid is dipropylene glycol methyl ether; the pigment is rutile titanium dioxide or cadmium yellow.
9. The quick-drying water-based sprayable road marking paint according to claim 1, characterized in that, The defoamer is one or more of polydimethylsiloxane, polyether-polysiloxane copolymer and C12-C14 fatty alcohol.
10. The method for preparing the quick-drying water-based sprayable marking paint according to any one of claims 1-9, characterized in that, The process involves mixing a hydroxy acrylic acid dispersion with deionized water, adding epoxy silane-modified nano-SiO2, a wetting and dispersing agent, and an antifoaming agent, then stirring. Next, microencapsulated stannous octoate, a tertiary amine co-catalyst, and a low-freezing-point film-forming aid are added and stirred again. Finally, hollow glass microspheres and pigments are added and stirred.